VIRTUAL SOCIETY: A NEW SPACE FOR SOCIAL IDENTITY FORMATION OR A FIELD OF ALIENATION? - Harahap, Rahma Hayati; Romasta, Romasta (Program Studi Pendidikan Soiologi Antropologi, FKIP-UNS, 2025)
The emergence of virtual society has created a new space for the formation of social identity that is fluid and performative. This study aims to analyze whether the online sphere provides freedom for identity expression or, conversely, fosters social alienation. Using a descriptive qualitative approach, this paper employs Erving Goffman's dramaturgical theory, Anthony Giddens’ concept of the reflexive self, and Karl Marx’s theory of alienation as its analytical framework. The findings reveal that identity in virtual society is shaped through continuous self-image negotiation, which can lead to a gap between the ideal self and the real self. The online space may serve as a platform for self-expression, yet it also has the potential to reinforce feelings of alienation, particularly when digital interactions replace genuine social closeness. This study highlights the importance of critical awareness in navigating the dynamics of identity formation in contemporary digital society. Keywords: Social identity, virtual society, dramaturgy, digital alienation, reflectivitas ABSTRAK Kemunculan masyarakat virtual telah membuka ruang baru bagi pembentukan identitas sosial yang bersifat cair dan performatif. Penelitian ini bertujuan untuk menganalisis apakah ruang daring memberi kebebasan ekspresi identitas atau justru menciptakan keterasingan sosial. Dengan pendekatan kualitatif deskriptif, tulisan ini menggunakan teori dramaturgi Erving Goffman, konsep “reflexive self” dari Anthony Giddens, dan teori alienasi Karl Marx sebagai kerangka analisis. Temuan menunjukkan bahwa identitas di masyarakat virtual dibentuk melalui proses negosiasi citra diri yang terus-menerus, namun berpotensi menimbulkan jarak antara diri ideal dan diri nyata. Ruang daring dapat menjadi wadah ekspresi, tetapi juga medan yang memperkuat perasaan keterasingan, terutama ketika interaksi digital menggantikan kedekatan sosial yang autentik. Penelitian ini menyoroti pentingnya kesadaran kritis terhadap dinamika pembentukan identitas dalam masyarakat digital kontemporer. Kata Kunci: Identitas sosial, masyarakat virtual, dramaturgi, alienasi digital, reflektivitas